2018
DOI: 10.18520/cs/v115/i10/1921-1927
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Potato Tuber Soft Rot using <i>N</i>-Acyl-L-Homoserine Lactone-Degrading Endophytic Bacteria

Abstract: Pectobacterium carotovorum (Pc) causing potato tuber soft rot uses N-acyl-L-homoserine lactones (AHLs) to control the production of virulence factors via quorum sensing (QS). Some bacteria produce enzymes to inactivate the AHL signals of pathogenic bacteria via a phenomenon known as quorum quenching. One hundred bacterial isolates from potato tubers were screened for AHL-degrading activity using biosensor strain Chromobacterium violaceum CV026. Of these isolates, 20 were able to inactivate AHLs from the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Variovorax can facilitate the interaction between plants and microorganisms by manipulating plant hormone levels to balance the growth of plant roots. V. paradoxus can significantly inhibit potato tuber soft rot and is considered to be a new type of potato tuber soft rot biological control agent ( Ha et al, 2018 ). In our study, the abundance of V. paradoxus in healthy root endophyte samples was high.…”
Section: Discussionmentioning
confidence: 99%
“…Variovorax can facilitate the interaction between plants and microorganisms by manipulating plant hormone levels to balance the growth of plant roots. V. paradoxus can significantly inhibit potato tuber soft rot and is considered to be a new type of potato tuber soft rot biological control agent ( Ha et al, 2018 ). In our study, the abundance of V. paradoxus in healthy root endophyte samples was high.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the use of QQ bacteria or QQ enzymes has appeared as an efficient tool for managing plant diseases ( Uroz et al, 2009 ). Several QQ strains such as Cupriavidus sp., A. lactucae , Burkholderia anthina , O. intermedium , Bacillus sp., Variovorax sp., Variovorax paradoxus , and A. tumefaciens have been discovered and applied as tools for the biocontrol of plant diseases ( Ha et al, 2018 ; Ye et al, 2019 , 2020b , c ; Fan et al, 2020 ). The expression of QQ hydrolytic enzymes (AttM and AiiA) quenched virulence in the pathogenic bacteria Dickeya spp.…”
Section: Discussionmentioning
confidence: 99%
“…The natural interactions between soil microorganisms, which may impact both pathogens and their hosts, can be considered to protect plants from soft rot [175]. There is an increasing emphasis on research dedicated to the discovery of new strains of bacteria active against soft rot disease, including, but not limited to, the genera Agrobacterium [176], Bacillus [160,[176][177][178][179][180][181][182][183][184][185][186][187], Bdellovibrio [188], Brevibacillus [185], Lactobacillus [177], Lellilottia [189], Ochrobactrum [190,191], Paenibacillus [192], Pseudomonas [178,179,183,184,186,[193][194][195][196], Rahnella [189], Rhodococcus [197][198][199], Serratia [110,189,200], Streptomyces [178,201,202], and Variovorax [176]. There are several reports of biocontrol strains against SRP of fungi: Aspergillus [203], Penicillium…”
Section: Pathogen Controlmentioning
confidence: 99%
“…Moreover, it has been suggested that the mixture of different types of AHLs is the most prominent method of induction of plant defenses [229]. Additionally, many biological control agents use quorum quenching (disruption of quorum sensing) as their mode of action against soft rot disease, e.g., Agrobacterium [176], Bacillus [176], Ochrobactrum [190,191], Rhodococcus [197][198][199], and Variovorax [176].…”
Section: Pathogen Controlmentioning
confidence: 99%